What purpose do national qualifications frameworks serve? : a look at other countries - Hanf, Georg [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2005)
"Looking at developments in other countries and at European level, this article outlines the objectives being pursued with the implementation of qualifications frameworks, what qualifications frameworks can do and possible approaches to them. Understood here as sets of skills, qualifications form the basic unit used in qualifications frameworks. Drawing on the examples provided by Ireland, England, Wales and Northern Ireland, the autors show how qualifications can be positioned in a hierarchical multi-level system with the help of descriptors in order to establish transparency and lateral mobility throughout an entire education system." (BIBB)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; T 1.5 International vergleichende Berufsbildungsforschung; Europäischer Qualifikationsrahmen; Qualifikationsniveau; Durchlässigkeit im Bildungssystem; Qualifikation; Anerkennung; Berufsbildungssystem; Internationaler Vergleich